Association between pretreatment neutrophil‐to‐lymphocyte ratio and immune‐related adverse events due to immune checkpoint inhibitors in patients with non‐small cell lung cancer. Issue 15 (26th June 2021) - Fujimoto, Airi; Toyokawa, Gouji; Koutake, Yoshimichi; Kimura, Shigeru; Kawamata, Yosei; Fukuishi, Kazuhisa; Yamazaki, Koji; Takeo, Sadanori
Abstract: Background: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of advanced or recurrent non‐small cell lung cancer (NSCLC). They cause immune‐related adverse events (irAEs), but the underlying mechanisms and predictors remain to be fully elucidated. In this retrospective study, we investigated the association between pretreatment neutrophil‐to‐lymphocyte ratio (NLR) and the occurrence of irAEs. Methods: The study involved 115 patients with NSCLC who started ICI‐only treatment in our hospital between January 2016 and April 2020. Results: Forty‐five patients (39.1%) had irAEs, and pretreatment NLR was significantly lower in the irAEs group than in the non‐irAEs group (2.8 vs. 4.1; p = 0.036). The cutoff value of the NLR was 2.86 (area under curve, 0.62; sensitivity, 0.56; specificity, 0.71), and the incidence rate of irAEs was significantly higher in the NLR < 2.86 group than in the NLR ≥2.86 group ( p = 0.004; odds ratio [OR]: 3.12; 95% confidence interval [CI]: 1.43–6.84). The multivariate analysis showed that the NLR was significantly associated with the occurrence of irAEs ( p = 0.016; OR: 2.69; 95% CI: 1.21–6.01). Conclusions: Low pretreatment NLR may be a predictive factor for the occurrence of irAEs. By focusing on the potential risk of irAEs in patients with a low pretreatment NLR, irAEs can be appropriately managed from an early period. Abstract : Here, we report that low pretreatment NLR may be a predictive factor for the occurrence of irAEs in NSCLC patients. The cutoff value of the NLR was 2.86, and the univariate and multivariate analysis showed that the NLR was significantly associated with the occurrence of irAEs.